Stability of the embankment of fine sand reinforced with geosynthetic materials - Lesov Kuvandik; Kenjaliyev Mukhamedali; Mavlanov Akhmadjan; Tadjibaev Sherzod (E3S Web of Conferences, 2021)
This research paper validates the significance of an assimilated attitude when choosing the design of the subgrade of railways constructed from fine sands in difficult engineering and geological conditions in the desert and steppe territories of Uzbekistan to ensure their sustainability with modern technologies and materials. The analysis of the results obtained in the calculations of the stability coefficient of the design structure of the embankment. The characteristics of the embankment soils correspond to the design data of the object "Removal of the existing railway section Dunguluk-Burgutli-Misken from the flood zone of the Shurbulak reservoir" The results of the calculations performed by the method of G. M. Shakhunyants, as well as the software "GEO 5" and "Plaxis 2D" show that the structure of the embankment with a height of more than 6 meters does not provide the required standard coefficient of stability. Complete warps of the embankment and graphs of changes in the stability coefficient of the design structure of the embankment, and with the laying of geotextiles as reinforcement of the pattern of the subgrade of railways, are given. Beneficial solutions to increase the stability coefficient of the embankment from fine sands are proposed, and the efficiency of using geosynthetic materials as a reinforcement of the pattern of the subgrade is substantiated. Theoretical calculations and analysis of prevailing embankment structures confirm the feasibility of reinforcing the structure of the subgrade erected from fine sands on the railway lines of Uzbekistan.